Rancang Bangun Prototype Sistem Monitoring Dan Kontrol Tanaman Hidroponik Berbasis Internet of Things (IoT) Menggunakan Microcontroller ESP32 - Veri Ferdiansyah; Siska Atmawan Oktavia Siska; Yudi Mulyanto; Yunanri.W (Bulletin of Information Technology (BIT), 2025)
Hydroponic farming has emerged as an innovative solution to address land limitations and support sustainable food production. However, its success highly depends on consistent monitoring of light intensity and nutrient water availability. This study aims to design and develop a prototype monitoring and control system for hydroponic plants based on the Internet of Things (IoT) using the ESP32 microcontroller. The system employs an ultrasonic sensor to measure water level, a Light Dependent Resistor (LDR) sensor to detect light intensity, a 12V DC water pump, and LED grow lights as actuators. Environmental condition data is transmitted in real-time to the Blynk mobile application, which also provides automatic notifications when anomalies occur, such as low water levels or light intensity falling below the threshold. The development method used is Research and Development (R&D) with the ADDIE model, covering analysis, design, development, implementation, and evaluation stages. Testing results show that the system operates automatically and in real-time, achieving 100% detection accuracy for water level measurements and 98% for light intensity measurements. The implementation of this prototype is expected to improve the efficiency and effectiveness of small-scale hydroponic cultivation and serve as an affordable solution for farmers and the general public to adopt smart farming technology.